A rare complication of percutaneous closure of coronary artery fistula: Inability to retrieve coil - Müslüm Şahin; Özkan Candan; Muhsin Türkmen (KARE Publishing, 2019)
Coronary fistulae may lead to coronary steal phenomenon or considerable volume overload on the cardiac chambers, causing significant hemodynamic problems. Coronary fistulae can be closed either surgically or percutaneously. Percutaneous closure is frequently performed with coil embolization or a vascular plug. Although percutaneous closure has significant advantages, such as a shorter duration of hospitalization and no sternal scarring, several complications, including coil embolization or failure to retrieve the device, may occasionally occur. In the current report, a patient with a left coronary to right atrium fistula who declined to have surgery underwent percutaneous coil embolization. However, after release of the coil, the catheter could not be retrieved using the standard anti-torque mechanism.